Efeitos de práticas de descompactação do solo em área sob sistema plantio direto - Seki, André Satoshi [UNESP]; Seki, Fernanda Gonçalves [UNESP]; Jasper, Samir Paulo; Silva, Paulo Roberto Arbex [UNESP]; Benez, Sérgio Hugo [UNESP] (GN1 Sistemas e Publicacoes, 2015)
Soil compaction is one of the limiting factors in areas subjected to direct seeding. The method used to break up the compacted layer should disturb the soil as little as possible, as well as maintain the ground cover. The aim of this study was to evaluate the influence of subsoiling, scarification and use of shaft-type furrowing mechanisms when sowing, on preserving the ground cover, water content and soil density, as well as the effects on maize yield in a dystroferic Red Nitosol, cultivated under a system of direct seeding for ten years. The experimental design was of randomised blocks, with eight soil management treatments: subsoiling to a depth of 0.40 m before sowing the winter crop, subsoiling to 0.40 m before sowing the maize, scarification to 0.30 m before the winter crop, scarification to 0.30 m before the maize, scarification to 0.20 m before the winter crop, scarification to 0.20 m before the maize, direct seeding of the maize with a shaft-type furrowing mechanism and direct seeding of the maize using a double disc furrower. There were four replications. Subsoiling and scarification influenced the preservation of the ground cover, soil density and water content immediately after sowing, but did not interfere in plant development or grain yield in the maize crop. The use of shaft-type furrowing mechanisms in the sowing operation had no effect on any of the parameters under study.
Effects of soil decompaction techniques in an area under a system of direct seeding
Keywords: Physical attributes; Productivity; Scarification; Subsoiling